Investigation of the road safety measures around schools in Ethekwini - Mhlanga, Mabuyi (Centre for Transport Studies, 2019)
Globally, road traffic injury is a leading cause of death and disability in children aged 15 to 19 and the second leading cause of death in children between the ages 10 to 14 years. This thesis reviewed literature regarding the extent of road traffic injuries involving child pedestrians, the risk factors for child pedestrians and the effectiveness of interventions aimed at road safety improvement. EThekwini Metro was used as a case study for investigating the magnitude of road traffic crashes involving child pedestrians around primary schools. The schools with the highest road traffic crashes were used to investigate the road and environment contributory factors to crashes and finally the interventions in place at these schools to reduce road traffic injuries. The magnitude of crashes was quantified by using road accident data obtained from eThekwini Metro and the investigation of the interventions applied at the schools was conducted using Google Earth imagery, onsite inspections and administering a questionnaire to educators at the schools chosen for the case study. Results suggest that, in eThekwini, 32% of pedestrian crashes involve children from 0 to 19 years. The 6 to 10 year age group has the highest risk of road traffic injury and boys are 20% more likely to be involved in a crash compared to girls. The top ten primary schools with the highest road traffic crashes are located in middle and low income areas in eThekwini, these are, Sydenham, Jacobs and Umlazi Township. Most crashes took place where three or more schools are located within a kilometre radius of each other. Child behaviour contributed to 77% of the road traffic crashes. Scholar transport driver behaviour was highlighted as a major contributor to crashes by the respondents and environmental factors that resulted in reduced visibility of the child pedestrian contributed to 6% of the crashes. The main cause of road traffic injury, 68%, was crossing the road when it was unsafe to do so. Most crashes took place away from the intersection (58%), under clear and dry weather conditions (95%) during daylight (87%), between 13h00 to 15h30 (41%). Mondays and Fridays had highest incidents of road traffic crashes compared to other days of the week. Forty five percent (45%) of crashes took place on Class 5 local roads but all top ten schools with the highest road traffic crashes are located within a kilometre of a Class 3 distributor road or a class 4 collector road and these higher order roads have the highest crashes per road associated with the primary schools in their vicinity. Traffic calming, in the form of speed humps are only provided on roads where school entrances are located and are not provided on other roads even the roads with the highest road traffic crashes. Pedestrian crossings that direct pedestrians to a safe crossing location, road signs and road markings that warn drivers about the school are also generally not provided. The study revealed that road safety education is not formally provided in the school’s curriculum, it is taught as part of the Life Skills subject. The content and type of training is decided upon by the Life Skills teachers. Practical training is only provided at two of the schools, in all other schools, road safety education is taught and tested in a classroom environment. The author recommends that further studies be conducted on child pedestrian road safety around schools to obtain a full understanding of the road and environmental risk factors, that the municipality adopts the school zone concept and develops a policy for road safety interventions within the school zones. The municipality must also constantly monitor road traffic crashes involving child pedestrians, collect necessary data and test the effectiveness of measures applied to reduce the risks for child pedestrian crashes, investigate the possibility of providing grade separated pedestrian crossing facilities on higher order roads within a kilometre radius of the schools, initiate a scholar transport driver training programme and to assist the schools in the provision of road safety education by providing facilities where practical road safety training can be taught.